Growth hormone secretagogue receptor signaling in the supramammillary nucleus targets nitric oxide-producing neurons and controls recognition memory in mice. (May 2022) - Aguggia, Julieta P.; Cornejo, María P.; Fernandez, Gimena; De Francesco, Pablo N.; Mani, Bharath K.; Cassano, Daniela; Cabral, Agustina; Valdivia, Spring; García Romero, Guadalupe; Reynaldo, Mirta; Fehrentz, Jean-Alain; Zigman, Jeffrey M.; et al.
Abstract: Ghrelin is a stomach-derived hormone that acts via the growth hormone secretagogue receptor (GHSR). Recent evidence suggests that some of ghrelin's actions may be mediated via the supramammillary nucleus (SuM). Not only does ghrelin bind to cells within the mouse SuM, but ghrelin also activates SuM cells and intra-SuM ghrelin administration induces feeding in rats. In the current study, we aimed to further characterize ghrelin action in the SuM. We first investigated a mouse model expressing enhanced green fluorescent protein (eGFP) under the promoter of GHSR (GHSR-eGFP mice). We found that the SuM of GHSR-eGFP mice contains a significant amount of eGFP cells, some of which express neuronal nitric oxide synthase. Centrally-, but not systemically-, injected ghrelin reached the SuM, where it induced c-Fos expression. Furthermore, a 5-day 40% calorie restriction protocol, but not a 2-day fast, increased c-Fos expression in non-eGFP+ cells of the SuM of GHSR-eGFP mice, whereas c-Fos induction by calorie restriction was not observed in GHSR-deficient mice. Exposure of satiated mice to a binge-like eating protocol also increased c-Fos expression in non-eGFP+ cells of the SuM of GHSR-eGFP mice in a GHSR-dependent manner. Finally, intra-SuM-injected ghrelin did not acutely affect food intake, locomotor activity, behavioral arousal or spatial memory but increased recognition memory. Thus, we provide a compelling neuroanatomical characterization of GHSR SuM neurons and its behavioral implications in mice. Highlights: SuM neurons express GHSR and are activated by centrally-injected ghrelin in mice. SuM neurons are activated in response to calorie restriction or HFD bingeing. A subset of GHSR neurons of the SuM expresses neuronal nitric oxide synthase. Intra-SuM-injected ghrelin increases recognition memory but not food intake.